Environmental Footprint Assessment of Methylene Blue Photodegradation using Graphene-based Titanium Dioxide - Kelvert Kong; Ying Weng; Weng Hoong Lam; Sin Yuan Lai (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
To date, photocatalysis has received much attention in terms of the degradation of organic pollutants in wastewater. Various studies have shown that graphene-based photocatalysts are one of the impressive options owing to their intriguing features, including high surface area, good conductivity, low recombination rate of electron-hole pair, and fast charge separation and transfer. However, the environmental impacts of the photocatalysts synthesis and their photodegradation activity remain unclear. Thus, this report aims to identify the environmental impacts associated with the photodegradation of methylene blue (MB) over reduced graphene oxide/titanium oxide photocatalyst (TiO2/rGO) using Life Cycle Assessment (LCA). The life cycle impacts were assessed using ReCiPe 2016 v1.1 midpoint method, Hierachist version in Gabi software. A cradle-to-gate approach and a functional unit of 1 kg TiO2/rGOwere adopted in the study. Several important parameters, such as the solvent type (ultrapure water, ethanol, and isopropanol), with/without silver ion doping, and visible light power consumption (150, 300, and 500 W) were evaluated in this study. In terms of the selection of solvent, ultrapure water is certainly a better choice since it contributed the least negative impact on the environment. Furthermore, it is not advisable to dope the photocatalyst with silver ions since the increment in performance is insufficient to offset the environmental impact that it caused. The results of different power of visible light for MB degradation showed that the minimum power level, 150 W, could give a comparable photodegradation efficiency and better environmental impacts compared to higher power light sources. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).